Literature Survey on Meteor Burst Communication System - Muhanned AL-RAWI (Bulletin of "Carol I" National Defense University, 2025)
A technology that has taken many years to develop is the foundation of Meteor-burst Communications (MBC). Many MBC systems have been installed and tested successfully. MBC systems comprise dynamic vehicular networks, fixed station networks, and point-to-point links. Currently available systems include medium data rate message handling, low data rate telemetry, and high-speed conversational voice advancements. In addition to describing the systems and technology currently being developed, this paper summarises earlier work in the field.